When multinationals leave: A CGE analysis of the impact of divestments - Antonio G. Gómez-Plana; María C. Latorre (Economics: The Open-Access, Open-Assessment E-Journal, 2014)
Most studies on Multinational Enterprises (MNEs) focus on the impact of their expansion through inward or outward foreign direct investment (FDI) flows. However, divestments are quite common among the operations of MNEs. In order to derive their effects, we build a computable general equilibrium (CGE) model that includes two non-standard characteristics: the presence of MNEs and unemployment. The model is applied to the Spanish economy, where FDI inflows have surpassed divestments at the aggregate level in the period 2005-2009, although divestments have been sizeable in ten sectors. We analyse two different scenarios: 1) divestments that involve the closure of plants of foreign affiliates and 2) divestments where national firms buy the plant of foreign affiliates. The model allows estimating the overall impact of the divestments occurring simultaneously in ten sectors and in particular sectors. Results not only show that national acquisitions are less harmful than closures, but quantify those effects, and provide information on the role of the divesting sector. Some adjustment costs arise in all scenarios.
Keywords: C68; F21; F23; 330; FDI; disinvestments; closures; national acquisitions; Spain